INCREASING STUDENTS’ GRAMMAR UNDERSTANDING USING LITERATURE : CLASSROOM ACTION RESEARCH AT MAN 1 PROBOLINGGO - Hidayat, Muhammad Ryan; Tirmidi, Tirmidi; Fauziyah, Mutammimatul (Jurnal Review Pendidikan dan Pengajaran, 2025)
This study aims to improve students’ grammar skills through literature-based instruction at MAN 1 Probolinggo. This research employed a Classroom Action Research (CAR) design. The participants consisted of 11 eleventh-grade students selected purposively. Data were collected through grammar tests administered before and after the intervention, supported by classroom documentation. The findings revealed that the students’ average pretest score (32.27) increased to 47.73 in the posttest, showing an improvement of 47.9%. This result indicates that literature-based instruction effectively enhances students’ understanding of grammatical structures—particularly simple present, simple past, and present continuous tenses—through contextual learning. The use of song lyrics such as Drunk Text, Cars Outside, and Photograph also fostered motivation and engagement throughout the lessons. Therefore, literature-based instruction is proven to be an effective approach to improving students’ grammar achievement and interest in English learning.